Comparison of effects of basalt and polyacrylonitrile fibers on toughness behaviors of lightweight aggregate concrete. (3rd May 2021) - Zeng, Yusheng; Tang, Aiping
Highlights: Forty-two specimens were design to test compressive and flexural behaviors. Two calculation methods were utilized to evaluate compressive toughness performance. Four methods form standards were utilized to evaluate flexural toughness performance. The optimal content of BF and PANF were suggested respectively. Abstract: To study the effects of fibers on the compressive and flexural toughness of lightweight aggregate concrete (LWAC), an experimental investigation of fiber-reinforced LWACs subjected to compressive and flexural loading conducted. In the study, basalt fibers (BFs) and polypropylene fibers (PANFs) are used as the reinforcing materials in 0.5%, 1.0%, and 1.5% volume fractions. The test results show that, except LYB0.5, BFs and PANFs can improve axial compressive strength, and BFs exhibit better improvement effect than PANFs under the same volume fraction. Moreover, compared to the plain LWAC specimen, the LWACs with BF and PANF reinforcements present better compressive stress–strain and flexural load–deflection behaviors, and the descending branches of these plots become curved with fiber addition. Additionally, the energy ratio method and the critical stress method are utilized to calculate the compressive toughness behaviors of the LWACs, respectively. And the calculation results demonstrate that at a particular fiber volume fraction, BFs improve the compressive toughness more than PANFs due to the higher tensile strength and elastic modulus. Moreover, energy ratio method is suggested to calculate compressive toughness. In addition, four methods from different standards are utilized to evaluate the flexural toughness behaviors of the LWACs. The comparative analysis results exhibit that the methods from ASTM C1609, JSCE SF-4, and JG/T 472-2015 can be used, whereas that from ASTM C1018 leads to some errors originating from the inaccurate determination of the first crack station of specimens. And specimen with 1% BF or 1.5% PANF are suggested to improve the flexural toughness behavior of LWACs respectively.